2014
DOI: 10.1093/mnras/stu2266
|View full text |Cite
|
Sign up to set email alerts
|

Active galactic nuclei at z ∼ 1.5 – I. Spectral energy distribution and accretion discs

Abstract: The physics of active super massive black holes (BHs) is governed by their mass (M BH ), spin (a * ) and accretion rate (Ṁ ). This work is the first in a series of papers with the aim of testing how these parameters determine the observable attributes of active galactic nuclei (AGN). We have selected a sample in a narrow redshift range, centered on z ∼ 1.55, that covers a wide range in M BH andṀ , and are observing them with X-shooter, covering rest wavelengths ∼1200-9800Å. The current work covers 30 such obje… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
138
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(151 citation statements)
references
References 62 publications
12
138
1
Order By: Relevance
“…This echoes the findings of J12 and of Elvis et al (1994), who use a similar proxy, L bol /L 2500Å . This suggests that the spread is larger than the ∼20 per cent stated in Capellupo et al (2015). This cannot be solely due to the ∼0.1 dex error on our mass estimate.…”
Section: Model Suitability and Implicationsmentioning
confidence: 49%
“…This echoes the findings of J12 and of Elvis et al (1994), who use a similar proxy, L bol /L 2500Å . This suggests that the spread is larger than the ∼20 per cent stated in Capellupo et al (2015). This cannot be solely due to the ∼0.1 dex error on our mass estimate.…”
Section: Model Suitability and Implicationsmentioning
confidence: 49%
“…Using this method to accurately measure the accretion rate, spin, inclination, and intrinsic reddening values would require exceptional data coverage and quality. Despite these uncertainties, our measurements of L bol are more accurate than those in other studies that lack X-ray spectra in addition to optical-NIR spectra (Capellupo et al 2015;Castelló-Mor et al 2016).…”
Section: Bh Spinmentioning
confidence: 63%
“…This is probably partly for the same reasons as discussed above-fewer Gaussian components in the decomposition lead to less degeneracybut additionally our SED continuum contains only one free parameter (the normalization), versus the Shen & Liu (2012) approach, which uses power-law continua (in some cases with a break included), with both normalization and slope left as free parameters. Mejía-Restrepo et al (2016) used the Capellupo et al (2015) data and models to directly compare results from performing a global decomposition with the AD model to those utilizing local power-law continuum fits, finding the global approach to be more reliable. Although our study is smaller, we have also shown that using our physical model of the underlying AGN continuum facilitates a global spectral decomposition that is at least consistent with alternatives.…”
Section: Spectral Decompositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the standard black body disc model depicted above, does not reproduce the observed soft X-ray emission seen in AGN, consequently other physical parameters are required such as black hole spin and/or substantial Compton upscattering (Laor et al 1997, but see also Capellupo et al 2015).…”
Section: Agn Accretion Disc Modelsmentioning
confidence: 99%